New records, taxonomic notes, and the description of a new species of Harpactorinae (Hemiptera: Heteroptera: Reduviidae) from French Guiana - Gil-Santana, Hélcio R. (Zootaxa, 2022)
Various genera and species of Harpactorinae (Hemiptera: Heteroptera: Reduviidae: Harpactorinae: Apiomerini and Harpactorini) occurring in French Guiana are treated. Diarthrotarsus guianensis sp. nov. (Harpactorini) is described. An updated key to the species of Diarthrotarsus Bergroth, 1905 is presented. Apiomerus nitidicollis Stål, 1872 and Sphodrolestes vittaticollis Stål, 1867 (both Apiomerini), Graptocleptes formosus Miller, 1951, Heza aurantia Maldonado, 1976, Heza phthinica Swanson, 2021, Isocondylus elongatus (Lepeletier & Serville, 1825), Notocyrtus costai Gil-Santana & Forero, 2009, Notocyrtus depressus Stål, 1872, Notocyrtus tibanae Costa & Gil-Santana, 2001 and Ploeogaster gesana Kirkaldy, 1909 (all Harpactorini) are recorded from French Guiana for the first time. The presence of Calliclopius nigripes (Linnaeus, 1767) (Apiomerini) and Heza sericans Stål, 1859 (Harpactorini) in French Guiana is confirmed. Photographs of the specimens studied are presented, with short taxonomical notes on all the recorded species. An illustrated redescription of the male genitalia of Notocyrtus tibanae is given.